Soccerology : unbelievable facts and stories about the beautiful game - Sylvester, Kevin (Annick Press, 2026)
"Uncover everything you never knew about the beautiful game in this vividly illustrated soccer compendium--from the science of a perfect backspin to soccer heroes who changed the sport forever. Colorful illustrations, fun infographics, and supercool trivia reveal all about the most-watched sport in the world. Begin with the game's startling origins or turn to any chapter and dive in! You'll discover historic firsts, trailblazing athletes, and the weirdest soccer records. Read unforgettable stories about players who pushed the boundaries of the game--sometimes by bending the rules. Learn why soccer had to become more inclusive before it could truly bring people together, and deepen your knowledge with easy-to-read charts, timelines, and further reading. Written and illustrated by former sports broadcaster and award-winning children's book author Kevin Sylvester, Soccerology is a must-have that's equally fascinating for soccer newbies and diehard fans."--